Four new earthworm species and subspecies belonging to genus Amynthas and Metaphire (Oligochaeta: Megascolecidae) from Hainan Island, China - Zhao, Qi; Jiang, Jibao; Sun, Jing; Qiu, Jiangping (Zootaxa, 2013)
Three new species and one new subspecies of earthworms from Hainan Island, China, are described: Amynthas dinganensis sp. nov., Amynthas tenuis sp. nov., Metaphire wuzhimontis sp. nov. and Metaphire magna minuscula subsp. nov. Amynthas dinganensis and Amynthas tenuis have two pairs of spermathecal pores in 5/6–6/7, and Metaphire wuzhimontis and Metaphire magna minuscula have two pairs of spermathecal pores in 7/8–8/9. COI and 16S gene fragments of the new species taxa have been sequenced. We provide comparisons between these new species taxa and related species using morphological and molecular characters.